Injunctive Norms or Descriptive Norms – Explaining Intention of Energy-Dense Food Intake among Adolescents - Sarintohe, Eveline (Utan Kayu Publishing, 2025)
This present study tested an extended Theory of Planned Behaviour (TPB) model including interaction effects between TPB determinants (i.e., attitudes, subjective norms/injunctive norms, perceived behavioural control (PBC), and intentions), and an additional variable (descriptive norms) among Indonesian adolescents. A cross-sectional study was done among 411 adolescents (Mage = 12.02 years, SD = 0.45, 53.3% boys) from five private schools in urban and suburban areas of Indonesia. Data were collected using adapted questionnaires. A Multiple Linear Regression was used to examine the associations and interaction between determinants (attitudes, injunctive and descriptive norms, and perceived behavioural control) and intention of energy-dense intake using R 4.0.2. Analyses demonstrated significant predictions of three determinants to intentions. Analysis showed that there was a significant difference in the regression to intentions between injunctive and descriptive norms, where descriptive norms more importantly explained intentions than injunctive norms. The results also showed that there were no significant two-way interactions. Injunctive norms and descriptive norms did not moderate the relation between attitude and intention, neither attitudes as moderator between PBC and intentions. All three determinants of TPB could predict the intention of eating energy-dense food. The TPB model could explain this behaviour. It looked likely beneficial to consider the difference between descriptive norms and injunctive norms (especially friends) that may strongly effect on high school students intentions to consume energy-dense food.